An investigation of the moderating effect of it personnel capability on the relationship between intangible it resources and it infrastructure flexibility on the sustainable competitive advantages - Lahcene, Makhloufi; Abu Al- Rejal, Hussein Mohammed Esmail; Mohtar, Shahimi (Asian Economic and Social Society (AESS), 2018)
IT personnel capabilities are regarded as the backbone of IS infrastructure and as the main top strategic issues among IT executives. The aim of this research is to explore the direct influence of Intangible IT Resources such as IT Knowledge Resources (ITKR), IT Relationship Resources (ITRR), and IT Governance (ITG) on Sustainable Competitive Advantages (SCA). The main question of this study is whether or not IT personnel capabilities are able to strengthen the relationship between VRIN resources such as (ITKR, ITRR, and ITG) and sustainable competitive advantages. Importantly, no published study has been examined this critical issue on how firms are able to generate VRIN resources that are the main driver of SCA. Thus, the objective of this re-search is to determine whether IT Personnel Capability has a direct and indirect effect (moderating role) in the relationship between intangible IT resources sustainable competitive advantages. This research applies quantitative survey for collection data among IT senior managers of Algerian high-tech industry. Findings, implications, and suggestions will be discussed.